Vivencias del adulto mayor en el grupo de cuidado de un hospital público de Chepén - Etchebarne Campos, Lourdes Daniela (2019)
This qualitative study aimed at comprehensively analyzing the human experience from the perspective of the elderly in the care of a public Hospital in Chepén group, which used the Phenomenology, based on the ideas of the philosopher Martin Heidegger in his work "Being and time". The setting was the "support Hospital Chepén, the number of participants in the research was formed by nine older adults who met the selection criteria, who conducted the interview in depth, which was recorded with the" permission of the interviewees. The findings suggest that older adults belonging to a group of care with people of their age, have experienced a change of positive characteristics, with regard to the activities carried out; This means that it is nice to be surrounded by people of his age, feel free, happy, more integrated, where Dasein of these older adults reveals the phenomenon "I feel good here", which comprises the being-in-the-world and thebe-with-the-others, going on in his life of the inauthentic authenticity given by the presence of its provision as being in the group, no matter the adversity; Seniors attend and feel good, always highlighting the pre-occupation/occupation, care & cure that exists of them by providing initial care, for his teammates.